THE DEGREE OF SPECIFICITY IN TEACHING LSAP VOCABULARY - VÎLCU, Dina (Studia Universitatis Babeș-Bolyai Philologia, 2024)
The Degree of Specificity in Teaching LSAP Vocabulary. Joining a long-running debate in the field of teaching and testing language for specific academic purposes (LSAP), the present study focuses on the degree of vocabulary specificity to be targeted in this type of courses. Researchers’ choices range between ‘pure’ general academic language and input with a high degree of specificity. The present study proposes a categorisation of vocabulary in the following groups: general (high and mid-frequency), general academic, border technical and technical. The category of border technical vocabulary proposed here includes words normally considered as belonging to general language levels B1 and B2, which are used frequently in a domain of study and only incidentally in others. Border technical and general academic vocabulary are proposed to be the focus of teaching and the object of assessment in the courses of specialised language, with technical language not excluded from the teaching process. Choosing the level of vocabulary specificity is one of the most difficult decisions the LSAP teacher needs to take in preparation of a course. He/She needs to consider factors like the available resources or the students’ familiarity with the domain. This study analyses the course of specialised language for humanities and arts in Romanian at Babeș-Bolyai University. Based on literature in the domain, on teaching experience and especially on student feedback, this study is hoped to contribute to setting the most adequate level of vocabulary specificity for different groups of learners, in contexts usually built on a multitude of variables, hardly in the teachers’ control. REZUMAT. Gradul de specificitate în predarea vocabularului în cursurile de limbaj pentru scopuri academice specifice. Alăturându-se unei îndelungate discuții în câmpul predării și testării limbajului pentru scopuri academice specifice (LSAS), prezentul studiu se axează asupra gradului de specificitate care poate fi vizat în cadrul acestui tip de cursuri. Alegerile cercetătorilor variază între limbajul academic general ‘pur’ și inputul cu un grad ridicat de specificitate. Acest studiu propune o împărțire a vocabularului în următoarele categorii: general (de frecvență mare și medie), academic general, tehnic de graniță și tehnic. Categoria vocabularului tehnic de graniță propusă aici include cuvinte considerate în mod normal ca aparținând nivelurilor de limbă generală B1 și B2 (putând fi înțelese și folosite, uneori, chiar la niveluri inferioare), dar care sunt folosite frecvent într-un domeniu de studiu și doar incidental în altele. Vocabularul tehnic de graniță și cel academic general sunt categoriile propuse ca focus al predării și obiect al evaluării în cursurile de limbaj specializat, fără a se exclude limbajul tehnic din procesul de predare. Alegerea nivelului de specificitate a vocabularului este una dintre cele mai dificile decizii pe care profesorul de LSAS trebuie să le ia atunci când își pregătește cursul. El/Ea trebuie să țină cont de factori precum resursele disponibile sau familiaritatea studenților cu domeniul. Acest studiu analizează cursul de limbaj specializat pentru științe umaniste și arte, în limba română, la Universitatea Babeș-Bolyai. Bazat pe literatura de specialitate, pe experiența de predare și mai ales pe feedbackul din partea studenților, se speră că acest studiu poate contribui la stabilirea celui mai adecvat nivel de specificitate a vocabularului pentru diferite grupuri de studenți, în contexte construite, de obicei, pe o multitudine de variabile, ce rareori sunt controlabile de către profesori. Cuvinte-cheie: limbaj pentru scopuri academice, limbaj specializat, specificitate, vocabular academic general, vocabular tehnic de graniță, științe umaniste și arte Article history: Received 10 January 2024; Revised 26 July 2024; Accepted 15 October 2024; Available online 10 December 2024; Available print 30 December 2024.